2021
DOI: 10.3390/beverages7040080
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception of Milk and Plant-Based Alternatives Added to Coffee

Abstract: Consumers have begun to use plant-based alternatives (PBAs) in their coffee instead of dairy products. PBAs can include soy milk, rice milk, coconut milk, almond milk, oat milk, and hemp milk. The objective of this study was to investigate consumer acceptability and sensory perception of coffee with added dairy milk and added oat, soy, and almond PBAs. Consumers (n = 116) that frequently add milk to their coffee (n= 58) and consumers that usually use PBAs (n = 58) were recruited to participate in the study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
1
20
1
Order By: Relevance
“…Gorman et al. (2021) also reported that sweetness increased consumers’ liking for plant‐based milk coffees, while sourness decreased it. This is probably because our sensory system evolved to detect and prefer specifically crucial nutrients such as the once rare energy (carbohydrate)‐rich plants that taste sweet (Mennella et al., 2016).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Gorman et al. (2021) also reported that sweetness increased consumers’ liking for plant‐based milk coffees, while sourness decreased it. This is probably because our sensory system evolved to detect and prefer specifically crucial nutrients such as the once rare energy (carbohydrate)‐rich plants that taste sweet (Mennella et al., 2016).…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Gorman et al. (2021) applied a check‐all‐that‐apply (CATA) questionnaire to investigate consumer perceptions of coffee with dairy milk and plant‐based milks (oat, soy, and almond). The terms in their study were based on a literature review of black coffee and plant‐based milks and evaluations by researchers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure for the sensory trial was adapted from Gorman and colleagues [ 31 ]. This study took place during the COVID-19 pandemic; therefore, participants were asked to self-identify if they had potential exposure to the virus or loss of smell and taste to ensure that health risks were minimized.…”
Section: Methodsmentioning
confidence: 99%